Osobennosti vozdejstvija sbivajušcich faktorov na vysokokvalificirovannych borcov s narušeniem slucha v sorevnovatel'noj dejatel'nost - Shevtsov, A. V.; Laptev, A. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2021)
he article deals with the features of confusing factors of persons with hearing impairments, specializing in Greco-Roman and freestyle wrestling. The analysis of their impact in the competitive activities of members of national teams in the declared types of wrestling is presented. The most significant confounding factors and their impact on the final competitive result are identified. Confounding factors of exogenous and endogenous nature, cause a negative impact on the mental state, the nature of behavior and the effectiveness of competitive activities of wrestlers. The identification of these factors makes it possible to improve the model of competitive activity of an athlete by introducing them into the training process.